Hypoglossal nerve stimulation in adolescents with down syndrome and obstructive sleep apnea: A systematic review and meta-analysis - Liu, Pan; Kong, Weiguo; Fang, Caijing; Zhu, Kangxu; Dai, Xiaohua; Meng, Xiangming (Frontiers in Neurology, 2022)
Objective To evaluate the efficacy and adverse effects of hypoglossal nerve stimulation in adolescents with down syndrome and obstructive sleep apnea. Methods A systematic search was conducted using PubMed, Web of Science, Embase, and Scopus databases. The systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive search strategy used a combination of Medical Subject Headings and free words with “OR” and “AND.” Articles were screened to extract data reporting apnea-hypopnea index, quality of life, voltage, follow-up duration, and complications. All included participants were adolescents with down syndrome and obstructive sleep apnea. Results A total of 92 articles were identified, of which 9 articles met the inclusion criteria. A total of 106 patients were included. All the studies showed that patients receiving hypoglossal nerve stimulation experienced a significant decrease in apnea-hypopnea index (at least 50%). The pooled AHI was significantly lower in patients following treatment (mean AHI reduction 17.43 events/h, 95% confidence interval 13.98–20.88 events/h, P < 0.001) after 2 case reports were excluded. The pooled OSA-18 were significantly decreased in 88 patients after treatment (mean OSA-18 reduction 1.67, 95% confidence interval 1.27–2.08, P < 0.001) after excluding 5 studies. Four investigations examined the necessity to optimize stimulation voltage for arousal during treatment. The most common complication was pain or discomfort in the tongue or mouth. Most studies had relatively short patient follow-up periods, with the most extended follow-up being 44–58 months. Conclusion Hypoglossal nerve stimulation significantly reduces apnea-hypopnea index and improves the quality of life; and thus, could be a potential alternative therapy for obstructive sleep apnea in adolescents with down syndrome. The adolescent's age, potential complications, adverse events, long-term efficacy, and comfort, needs to be considered while performing hypoglossal nerve stimulation.